Equality, History and an End to Whiteness - Craig B. Howley; James Clifton; Aimee Howley (Journal of Research in Rural Education, 2018)
Research in education, but notably also in history (as James suggests here), is much better conceived and practiced as a kind of conversation than as a scheme for outing the facts. Of course, some colleagues (particularly in education) think otherwise! But when it comes to something that means something"a connective structure of facts and ideas and commitments, for instance"any fi nal determination of fact is premature. Interpretations of this sort ("research") need reason (and reasons) and voices (and voice). Giving voice in this way"articulating facts, ideas, and commitments"is tremendously diffi cult: an acquired taste perhaps; but one that anyone might acquire.